COMPARATIVE COMPRESSIBILITY AND EQUATION OF STATE OF ORTHORHOMBIC AND TETRAGONAL EDINGTONITE - Gatta G.D.; Boffa Ballaran T.; Comodi P.; Zanazzi P.F. (My University, 2004)
The high-pressure (HP) behaviour of a natural orthorhombic and tetragonal edingtonite from Ice River, Canada, has been investigated using in situ single-crystal X-ray diffraction. The two isothermal equations of state up to 6.74(5) GPa were determined. V 0, KT0 and K′ refined with a third-order Birch–Murnaghan equation of state (BM-EoS) are: V 0 = 598.70(7) Å3, KT0 = 59(1) GPa and K′=3.9(4) for orthorhombic edingtonite and V 0 = 600.9(2) Å3, KT0 = 59(1) GPa and K′=4.2(5) for tetragonal edingtonite. The experiments were conducted with nominally hydrous pressure penetrating transmitting medium. No overhydration effect was observed within the pressure range investigated. At high-pressures the main deformation mechanism is represented by cooperative rotation of the secondary building unit (SBU).Si/Al distribution slightly influences the elastic behaviour of the tetrahedral framework: the SBU bulk moduli are 125(8) GPa and 111(4) GPa for orthorhombic and tetragonal edingtonite, respectively. Extra-framework contents of both zeolites show an interesting behaviour under HP conditions: the split Ba2 site at P >2.85 GPa is completely empty; only the position Ba1 is occupied. Electronic Supplementary Material. Supplementary material to this paper (Observed and calculated structure factors) is available in electronic form at http:// dx. doi. org/ 10. 1007/ s00269-004-0394-y.
Keywords: Orthorhombic and tetragonal edingtonite; High-pressure single-crystal X-ray diffraction; Comparative compressibility